Penerapan Model Problem Based Learning Untuk Meningkatkan Motivasi Belajar Siswa Dengan Media Konkret Papan Ludo Kelas 5 SD Negeri Sendangmulyo 02 Semarang (psnppg, 2025)
Classroom action research was carried out in class 5 of SDN Sendangmulyo 02 Semarang with research subjects of 28 students. This research was conducted in two cycles, namely cycle I and cycle II. Each cycle consists of four stages, namely planning, implementation, observation and reflection. Data collection techniques in this research are tests, interview guidelines, observation guidelines, and documentation. The data analysis technique uses classroom action research with quantitative and qualitative analysis. The results of research conducted by researchers show that there has been an increase in students' learning motivation with the theme Indonesiaku Kaya Raya. Learning Motivation in the knowledge aspect increased in the science content of cycle I, obtaining classical completeness of 59.25% and cycle II experienced an increase of 88.88%. In the IPAS content, cycle I obtained classical completeness of 55.55% and cycle II obtained 85.18%. Based on the results of classroom action research that was carried out on grade 5 students at SDN Sendangmulyo 02 Semarang, it can be concluded that through the application of the Problem Based Learning model assisted by the concrete media of the ludo board, students' learning motivation can be increased.
Keywords: Problem Based Learning Model; Learning Motivation; Ludo board concrete media